Pengaruh Sistem Pengendalian Manajemen Terhadap Kinerja Manajerial Pada Bank Perkreditan Rakyat Karangmalang Sragen - Nur Haryono, Prisuda; , Dr. Erma Setiawati, Ak, MM (2016)
The purpose of this study was to analyze the influence of management control systems to managerial performance in Bank Perkreditan Rakyat Karangmalang Sragen . This study used survey method using primary data obtained from the questionnaire . This study population is all employees of Bank Perkreditan Rakyat Karangmalang Sragen. The sample used in this study are all managers of Bank Perkreditan Rakyat Karangmalang Sragen the number of respondents 47 respondents . The sampling technique used is the technique of saturated samples . This study uses linear regression analysis . These results indicate that the system of management control effect on managerial performance in Bank Perkreditan Rakyat Karangmalang Sragen.